أثر تمكين العاملين في أبعاد التطوير التنظيمي في المؤسسة الاقتصادية دراسة حالة الصندوق الوطني للتضامن الاجتماعي cnas الوادي - صحراوي, ميمية; لعجالي, سناء (University of eloued جامعة الوادي, 2018)
تهدف هذه الدراسة إلى معرفة أثر تمكين العاملين في أبعاد التطوير التنظيمي في المؤسسة الاقتصادية، وكذا التعرف على مستوى كل من تمكين العاملين وأبعاد التطوير التنظيمي في المؤسسة محل الدراسة ومدى وجود فروق ذات دلالة احصائية على مستوى متغيرات الدراسة تعزى للمتغيرات الشخصية. ولتحقيق ذلك قمنا بإسقاط الدراسة النظرية في الجانب الميداني أين تمت على مستوى الصندوق الوطني للضمان الاجتماعي للعمال الأجراء بمديرية الوادي بالشط، والتي كانت أداتها الرئيسة الاستمارة، التي وزعت على 40 موظفا من المؤسسة وقد تم معالجة معلوماتها باستخدام البرنامج الاحصائي الــــــــــSPSS. وكان من بين أهم نتائج الدراسة المتوصل إليها : وجود أثر ذو دلالة احصائية بين تمكين العاملين وأبعاد التطوير التنظيمي عند مستوى دلالة 0.05، و أيضا وجود علاقة ارتباط معنوية بين تمكين العاملين وأبعاد التطوير التنظيمي، ومن خلال هذه النتائج تم التوصل إلى جملة من الاقتراحات أهمها: ضرورة اهتمام المؤسسة أكثر بإحداث تطوير تنظيمي على مستوى جماعات العمل، وخلق تطوير تنظيمي على المستوى الفردي. The aim of this study is to know the impact of the empowerment of workers in the dimensions of organizational development in the economic institution, as well as to identify the level of both the empowerment of workers and the dimensions of organizational development in the institution under study and the existence of differences of statistical significance at the level of study variables attributed to personal variables. In order to achieve this, we have attached the theoretical study to a field study conducted by the National Fund for Social Security for Workers in ELOUAD - Al-Shat- Directorate, whose main tools were the form, which was distributed to 40 employees from the Foundation, whose information was processed using the SPSS. : The most important results of the study were - There is a significant statistical effect between the empowerment of employees and the dimensions of organizational development at the level of significance of 0.05. - There is also a significant correlation between the empowerment of employees and the dimensions of organizational development. More by creating organizational development at the level of working groups,and creating organizational development at the individual level
مذكرة ماستر ادارة اعمال
Keywords: تمكين العاملين ، التطوير التنظيمي ، ابعاد التطوير التنظيمي.